The Relationship Between Spiritual Well-Being and Frequency of Antenatal Care (ANC) Visits with Anxiety in Pregnant Women During the Third Trimester at Singkawang Tengah II Public Health Centers - Hidayah, Hidayah; Wardati, Weni; Surtikanti, Surtikanti; Makmuriana, Lestari; Mardiyani, Ridha (Universitas Malahayati, 2023)
ABSTRACT Pregnancy is an important period in a woman's life. The physical and emotional changes that occur during this time can trigger excessive anxiety, especially in the third trimester, especially before childbirth, which is 107,000 or 28.7%. The frequency of maternal visits to check on her pregnancy (ANC) and the condition of her spiritual well-being are important keys to overcoming anxiety. There is a gap between K1 and K4 coverage of 7.9%. Anxiety that occurs during pregnancy can lead to hypertension, premature birth, and low birth weight. This study aims to determine the direct relationship between spiritual well-being and frequency of ANC with anxiety before childbirth in third-trimester pregnant women at the Singkawang Tengah II Public Health Center. The research type is descriptive quantitative using a correlational method approach.The sample size was 62 respondents using a consecutive sampling technique.The instrument adopted the Pregnancy-Related Anxiety Questionnaire (PRAQ-R2) and a modification of the Spiritual Well-being Scale (SWBS).The statistical test used was Spearman Rank (rho). Characteristics of respondents include 53 people (85.5%) are in the age category that is not at high risk for pregnancy (20-35 years), have a secondary education background (SMU / SMK), as many as 33 people (53.2%) and respondents do not work as many as 52 people (83.9%). A high percentage of respondents (61.3%) had moderate spiritual well-being, with the frequency of ANC visits fulfilled by 44 people (71.0%), and the anxiety level of 38 people (61.3%) was in a low category. There is a significant negative relationship between spiritual well-being and anxiety, as evidenced by the correlation coefficient of 0.385 with p-value=0.002 (p<0.05), and there is a meaningful negative relationship between frequency of ANC visits and anxiety, as evidenced by the correlation coefficient of 0.308 with p-value=0.015 (p<0.05). Spiritual well-being and antenatal care visits negatively correlated with a weak strength of correlation to the level of anxiety in pregnant women. The closer the mother is to God, the more she is willing to undergo trials during pregnancy which gives her peace of mind. Completing ANC increases the mother's understanding of pregnancy and childbirth to reduce anxiety. Keywords : Spiritual Well-Being, Anxiety, ANC, Pregnancy. ABSTRAK Kehamilan adalah masa yang penting dalam hidup seorang wanita. Perubahan fisik dan emosional yang tejadi dimasa ini dapat memicu kecemasan berlebih khususnya pada trimester ketiga, terlebih menjelang persalinan yaitu sebesar 107.000 atau 28,7%. Frekuensi kunjungan ibu dalam memeriksakan kehamilannya (ANC) dan kondisi kesejahteraan spiritual yang dimiliki ibu menjadi kunci penting dalam mengatasi kecemasan. Faktanya, terdapat kesenjangan antara cakupan K1 dan K4 sebesar 7,9%. Kecemasan yang terjadi dimasa kehamilan dapat mengakibatkan hipertensi, kelahiran prematur dan berat lahir rendah. Penelitian ini bertujuan untuk mengetahui hubungan langsung antara kesejahteraan spiritual dan frekuensi ANC dengan kecemasan menjelang persalinan pada ibu hamil trimester tiga di Puskesmas Singkawang Tengah II. Jenis penelitian ini adalah deskriptif kuantitatif dengan menggunakan pendekatan metode korelasional. Jumlah sampel sebanyak 62 responden dengan menggunakan teknik consecutive sampling. Instrumen yang digunakan mengadopsi kuesioner Pregnancy Related Anxiety Questionnaoire (PRAQ-R2) dan modifikasi dari Spiritual Well-being Scale (SWBS). Uji statistik yang digunakan adalah Rank Spearman (rho). Karakteristik responden meliputi 53 orang (85,5%) berada dalam kategori umur yang tidak beresiko tinggi untuk hamil (20-35 tahun), latar belakang pendidikan menengah (SMU/SMK) sebanyak 33 orang (53,2%) dan responden tidak bekerja sebanyak 52 orang (83,9%). Sebanyak 61,3% responden memiliki kesejahteraan spiritual sedang dengan frekuensi kunjungan ANC terpenuhi sebanyak 44 orang (71,0%) dan tingkat kecemasan sebanyak 38 orang (61,3%) berada pada kategori rendah. Terdapat hubungan negatif yang bermakna antara kesejahteraan spiritual dengan kecemasan, dibuktikan dari nilai koefisien korelasi sebesar 0,385 dengan p-Value=0,002 (p<0,05) dan terdapat hubungan negatif yang bermakna antara frekuensi kunjungan ANC dengan kecemasan, dibuktikan dari nilai koefisien korelasi sebesar 0,308 dengan p-Value=0,015 (p<0,05). Kesejahteraan spiritual dan kunjungan ANC berkorelasi negatif dengan kekuatan korelasi yang lemah terhadap tingkat kecemasan pada ibu hamil. Semakin dekat ibu dengan Tuhannya semakin ibu ikhlas menjalani ujian selama kehamilan yang membuatnya tenang. Terpenuhinya ANC meningkatkan pemahaman ibu tentang kehamilan, dan persalinan sehingga mampu mengurangi kecemasan. Kata Kunci: Kesejahteraan Spiritual, Kecemasan, ANC.